Effects of medication, treatment, and behavioral beliefs on intentions to take medication in patients with familial hypercholesterolemia - Hagger, Martin; Hardcastle, Sarah; Hu, M.; Kwok, S.; Lin, J.; Nawawi, H.; Pang, J.; Santos, R.; Soran, H.; Su, T.; Tomlinson, B.; Watts, G. (Elsevier Ireland, 2018)
Background and aims: Although familial hypercholesterolemia (FH) can be effectively managed using cholesterol-lowering medication, patients often fall short of complete treatment adherence. Identifying the psychological factors associated with self-regulation of FH medication is important to inform interventions to maximize adherence. The aim of the present study was to test an integrated psychological model in predicting FH patients' intentions to take medication. Methods: FH patients attending clinics in seven countries were invited to participate in a cross-sectional survey study. Consenting patients (N = 551) completed self-report measures of generalized beliefs about medication overuse and harms, beliefs in treatment effectiveness, specific beliefs about taking medication (attitudes, subjective norms, perceived behavioral control), and intentions to take medication. Participants also completed measures of demographic variables (age, gender, education level, income, cardiovascular disease status). Data were analysed using path analysis controlling for country and demographic variables. Results: Attitudes (ß = .331, p<0.001), subjective norms (ß = .121, p=0.009), and beliefs about medication overuse (ß = -.160, p<0.001) were significant predictors of intentions to take medication. Treatment beliefs predicted intentions indirectly (ß = .088, p<0.001) through attitudes and subjective norms. There was also an indirect effect of beliefs about medication overuse on intentions (ß = -.045, p=0.056), but the effect was small compared with the direct effect. Conclusions: The findings indicate the importance among FH patients of specific beliefs about taking medication and generalized beliefs about medication overuse and treatment in predicting medication intentions. When managing patients, clinicians should emphasize the efficacy of taking cholesterol-lowering drugs and the importance of treatment outcomes, and allay concerns about medication overuse.